(Invited) Pixel-Parallel 3-D Integrated CMOS Image Sensors for Next-Generation Video Systems. (10th April 2018) - Goto, Masahide; Honda, Yuki; Watabe, Toshihisa; Hagiwara, Kei; Nanba, Masakazu; Iguchi, Yoshinori; Saraya, Takuya; Kobayashi, Masaharu; Higurashi, Eiji; Toshiyoshi, Hiroshi; Hiramoto, Toshiro
Abstract : We report 3-D integrated CMOS image sensors with pixel-parallel A/D converters (ADCs). Direct bonding of silicon-on-insulator (SOI) wafers with gold electrodes embedded in a SiO2 surface achieves high-density pixel-wise interconnection in the sensor. Prototype 128 × 96 resolution sensors are developed on two SOI wafers with 16-bit ADCs for pulse frequency output integrated in every pixel. We have confirmed successful operation of capturing video images of 16-bit digital output and a wide dynamic range of 96 dB, demonstrating this type of 3-D integration provides functional diversification including circuits, sensors, and More-than-Moore type devices.